Association between Gestational Diabetes Mellitus and Pregnancy Outcomes - Sultana, Aklima; Kazal, Rezaul Karim; Selim, Shahjada; Das, Tripti Rani; Mahmood, Sharmeen; Nazneen, Sabiha; Ahmed, Ahsanara Binta; Sultana, Most Tahmina (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Pregnancy induces physiological lipid changes, which are amplified in the setting of hyperglycemia. Gestational diabetes mellitus (GDM) is associated with dyslipidemia that may contribute to adverse fetomaternal outcomes. This study compared the fetomaternal outcomes between pregnant women with GDM in their third-trimester and those in women with normal pregnancy in order to determine the association between GDM and pregnancy outcomes. Methods: In this prospective observational study, 182 pregnant women in the third trimester were enrolled, comprising 112 cases with GDM and 70 controls without GDM, at Bangladesh Medical University, Dhaka. Fasting lipid panels were obtained in the third trimester and were analyzed. Dyslipidemia was defined using conventional criteria TC ≥ 200 mg/dL, LDL-C ≥ 130 mg/dL, TG ≥ 150 mg/dL, HDL-C < 50 mg/dL and a composite TG: HDL-C ratio > 3.5. Participants were followed for maternal and perinatal outcomes, including PIH/preeclampsia, preterm birth, Apgar scores, NICU admission, and birth weight. Results: Compared with controls, the GDM group exhibited higher serum TC and TG, and a higher TG: HDL-C ratio in the third trimester (p-values for TC = 0.008, TG = 0.013, TG: HDL-C ratio = 0.025). The prevalence of dyslipidemia TC ≥ 200 mg/dL, TG ≥ 150 mg/dL, or LDL-C ≥ 130 mg/dL was greater among cases, p = 0.002, 0.009, and 0.002, respectively, with TG: HDL-C > 3.5 significantly more frequent in the GDM group (p = 0.004). Maternal outcomes showed higher incidence of PIH (14.3% vs. 0% and preeclampsia 12.5% vs. 1.4%) in cases (p = 0.001 and p = 0.008). Perinatal outcomes revealed higher rates of low-birth-weight (LBW) and preterm birth in the GDM group (p = 0.001 and p = 0.005). Apgar scores < 7 at birth were more common among cases (p = 0.033). Although Neonatal Intensive Care Unit (NICU) admission, SGA, and LGA did not differ significantly, a trend toward adverse neonatal outcomes was observed in GDM pregnancies with dyslipidemia. Conclusion: Third-trimester dyslipidemia, particularly elevated TG and TG: HDL-C ratio, is more prevalent in pregnancies affected by GDM and is associated with increased maternal hypertensive disorders and adverse perinatal outcomes. The TG: HDL-C ratio emerges as a potential surrogate marker of dyslipidemia-related risk beyond glycemic assessment. Integrating lipid profiling into GDM management could enhance risk stratification and guide targeted obstetric surveillance and postpartum cardiovascular risk mitigation. Ibrahim Cad Med J 2025, 15(1): 21-27